In Utero Bisphenol A Exposure Induces Abnormal Neuronal Migration in the Cerebral Cortex of Mice - Ling, Wenting; Endo, Toshihiro; Kubo, Ken-ichiro; Nakajima, Kazunori; Kakeyama, Masaki; Tohyama, Chiharu (Frontiers in Endocrinology, 2016)
Bisphenol A (BPA) has been known to have endocrine disrupting activity to induce reproductive and behavioral abnormalities in offspring of laboratory animal species. However, morphological basis of this abnormality during brain development is largely unknown. Cerebral cortex plays a crucial role on higher brain function, and its precisely laminated structure is formed by neuronal migration. In the present study, transfecting a plasmid (pCAG-mCherry) by in utero electroporation (IUE), we visualized developing neurons and investigated the possible effects of in utero BPA exposure on neuronal migration. Pregnant mice were exposed to BPA by osmotic pump at estimated daily doses of 0, 40 (BPA-40), or 400 (BPA-400) μg/kg from embryonic day 14.5 (E14.5) to E18.5. IUE was performed at E14.5 and neuronal migration was analyzed at E18.5. Compared with the control group, neuronal migration in the cortical plate was significantly decreased in the BPA-40 group; however, there was no significant difference in the BPA-400 group. Among several neuronal migration related genes and layer specific genes, TrkB in the BPA-400 group was found significantly upregulated. In conclusion, in utero exposure to low BPA dose was found to disrupt neuronal migration in the cerebral cortex in a dose specific manner.